Thermal and Acoustic Properties of Aerogels: Preliminary Investigation of the Influence of Granule Size. (March 2017) - Moretti, Elisa; Merli, Francesca; Cuce, Erdem; Buratti, Cinzia
Abstract: The influence of granules size in silica aerogels is experimentally investigated in terms of thermal and acoustic performance characteristics. The transmission loss (TL) is measured at normal incidence in a traditional impedance tube, whereas the thermal conductivity (λ) is evaluated using a Hot Plate apparatus, setting up an appropriate methodology, due to the nature of the sample. The results reveal that the small granules (granules size in the 0.01-1.2 mm range), which have the highest density, have the best performance both in terms of thermal and acoustic properties. Depending on the granules size, λ varies in 19-22 mW/mK range at 10 °C, whereas a TL equal to 13 dB at about 6400 Hz for 20 mm thickness is obtained for small granules.